Sdom gsum rab dbyeʼi kha skoṅ rtsa ʼgrel : a supplementary text of the Sdom gsum rab dbye, Sa-skya Paṇḍita Kun-dgaʼrgyal-mtshan's treatise on the three disciplines of Buddhism, and its detailed commentary - Go-rams-pa Bsod-nams-seṅge, 1429-1489 (T.G. Dhongthog Rinpoche, 1978)
On the three disciplines of Buddhism and the relationship between the three vehicles (yāna)